HUBUNGAN PENGETAHUAN DAN SIKAP LANSIA DENGAN PEMANFAATAN POSYANDU LANSIA DI DESA UJUNG LABUHAN KECAMATAN NAMORAMBE KABUPATEN DELI SERDANG TAHUN 2021 - Nismala Dewi; Eva Ratna Dewi; Edy Marjuang Purba (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
WHO in 2018 noted that of the 675 million elderly deaths in the world due to degenerative diseases, 225 million (33.33% proportion) were in developed countries and 450 million (66.66 proportions) were in developing countries. The elderly population is estimated at almost 600 million people, which is projected to be 2 billion in 2050. Problems that often occur in the elderly include physical changes: cell decline, changes in the cardiovascular system, decreased respiration. Efforts to improve the health status of the elderly in the community are through Posyandu services for the elderly. Utilization of Posyandu for the Elderly is low even though it provides the benefits needed for the health of the elderly. This study is an analytic observational study with a cross sectional approach to analyze whether or not there is a relationship between knowledge and attitudes of the elderly with the use of posyandu for the elderly. The elderly population in Ujung Labuhan Village, Namorambe District, Deli Serdang Regency in 2021, as many as 72, the sample was taken by purposive sampling with a total of 45 elderly. Data analysis using chi square test. Most of the respondents have a low level of knowledge, namely 26 respondents (57.8%), a small proportion have good knowledge, 19 respondents (42.2%). Most of the respondents had a positive attitude towards the elderly posyandu as many as 23 people (51.1%), a small number of respondents had a negative attitude as many as 22 people (48.9%). Based on the results of the chi square test, it is known that the value of p = 0.000 <0.05 means that there is a relationship between attitudes and the use of posyandu for the elderly. There is a relationship between knowledge and attitudes of the elderly with the use of posyandu for the elderly. The elderly population in Ujung Labuhan Village, Namorambe District, Deli Serdang Regency in 2021. It is hoped that health workers will take a more innovative approach in providing health services to the elderly while still implementing health protocols.